Haoma: unveiling the mysteries of Iran's sacred Zoroastrian botanical wonder - Zarei Karyani, Tayebeh; Yousefzadi, Morteza; Sheikhakbari-Mehr, Reza (Ethnobotany Research and Applications, 2025)
Background: The Zoroastrian plant haoma has sparked extensive scholarly debate within history, botany, and religious studies. Its identity and cultural significance remain pivotal in discussions surrounding Indo-Iranian religious traditions. This review synthesizes historical, botanical, and religious perspectives to enhance understanding of Haoma’s role in Indo-Iranian traditions. Methods: This study adopts a systematic review approach, synthesizing information from historical texts, archaeological findings, and ethnobotanical research. Key sources include the Avesta, Vedic literature, and comparative Indo-Iranian mythology. The study also incorporates modern phytochemical analyses of proposed botanical candidates to assess their plausibility in historical religious use. By comparing linguistic similarities and cross-cultural applications of sacred plants, the review evaluates the likelihood of various species representing the historical Haoma. Results: Haoma serves as a vital symbol of immortality, purity, and divine connection in Zoroastrian rituals. While various identifications exist, the research endorses Ephedra due to its historical importance and psychotropic properties, highlighting parallels with the Vedic Soma and emphasizing the broader religious implications of sacred plant compounds. Furthermore, the role of haoma has evolved, maintaining relevance in contemporary Zoroastrian practices and academic discourse. Conclusions: This study addresses knowledge gaps by reexamining haoma's botanical and religious significance. Although Ephedra remains a strong candidate, further interdisciplinary exploration is essential to address uncertainties. By employing modern methodologies, this review enhances our understanding of haoma's enduring impact on religious and cultural history. Keywords: Haoma, Cultural heritage, Ethnobotany, Zoroastrianism, Sacred drink